SELF-EFFICACY OF STROKE PATIENTS AT THE INPATIENT INSTALLATION ROOM OF SURABAYA HAJI GENERAL HOSPITAL - Jumain Main; Rachmat Hargono; Abu Bakar (Alta Dharma Publisher, 2019)
Stroke is a nerve function disorders that impact on the quality of life. This study aimed to describe the level of self-efficacy among stroke patients at the Inpatient Installation room of Surabaya Haji Hospital. A descriptive survey study was applied in this study. Seventy samples were selected by using a consecutive sampling technique. The investigation started from February 20 to March 20, 2019. Data were analyzed using descriptive statistics. The results reported that most of the patients were low self-efficacy (70,0%), while 30% of patients were moderate self-efficacy (30,0%). In conclusion, it showed that the majority of patients were low self-efficacy and need to be considered by healthcare providers before designing the nursing intervention. Keywords: self-efficacy, stroke patients